Etika Svetog Klimenta Ohridskoga - Obrazovanjem do razumjevanje svijeta kao manifestacija Boga - Donev, Dejan (Hrvatsko filozofsko društvo & Filozofski fakultet Sveučilišta u Splitu, 2009)
The culture and its results depends and on the ethics of people that represent it. This claim bases on the experience from the creation of culture from territory from which I origin and which giving a literacy to the very important part of Europe gave them and a way of understanding the world. That kind of ethics is the ethics of St. Climent (mostly known in international literature as St. Clement from Ohrid)... In the moment when God bless us with ability to write and read, in the same moment it blessed us with the obligation of doing good (well) to the others. In another words, He blessed us with ability to recognize that if we want to rich Him, we must avoid evil. Understanding this it wasn’t difficult for St. Climent to go step forward from the pure acceptance of the general ethical postulate, announcing: it isn’t enough to run from the evil acting, but in the same time we must dedicate ourselves of doing good. This brings him to the ethics of acting which is: - ethics of offering knowledge’s; - through knowledge to God in ourselves for God for ourselves; - ethics of creation personal identities and recognizing and respecting others identities and sovereignty; - absence of interdisciplinary based thinking of this kind of role of ethics in this territories and the consequences from this as a possibility for global conflict of cultures.
The ethics of st. Climent of Ohrid, or education as a way of understanding the world as a manifestation of god
Keywords: St. Climent from Ohrid, education, ethics, literacy